Detecting Microsurgical Complications with ViOptix Tissue Oximetry in a Pediatric Myocutaneous Free Flap: Case Presentation and Literature Review - Kozusko, Steven D.; Gbulie, Uzoma B. (Journal of Reconstructive Microsurgery Open, 2018)
Background Microvascular compromise from arterial or venous occlusion is a common cause of free flap failure. The salvage rate following a microvascular compromise is dependent on detecting the problem early and intervening quickly.Methods The ViOptix tissue oximeter measures tissue oxygen saturation using the near-infrared spectroscopy technology. The ViOptix device has an alarm capability to warn of potential compromise to tissue perfusion. The tissue oximetry readings are visible on the bedside monitor and are relayed to a webpage link, which is accessible on a personal computer or mobile device, allowing real-time monitoring. This article presents a case where real-time monitoring allowed almost immediate detection of inadvertent pedicle compromise allowing flap salvage by repositioning without surgical intervention.Results In the case presented, the patient's nurse inadvertently positioned a pillow under the location of the vascular pedicle likely causing microvascular compression. The ViOptix reading dropped and for this reason the nurse contacted the Plastic Surgery team. The drop was confirmed remotely and the flap was urgently evaluated in person. Once the pillow was removed, the ViOptix readings normalized and Doppler signals strengthened in the flap.Discussion While tissue oximetry monitoring does not by itself ensure flap survival, it provides critical information than conventional flap monitoring would allow giving the microsurgeon the opportunity to make a quicker decision. ViOptix tissue oximeters are able to detect vascular compromise even before conventional clinical symptoms are present. Alas in several cases by the time clinical symptoms develop the flap may be beyond salvage.
Keywords: microsurgeon; tissue oximetry; near-infrared spectroscopy